A review of the family ergasilidae (copepoda: poecilostomatoida) of Africa - Andrews, Melanie (University of the Free State, 2004)
Ten Ergasilus von Nordmann, 1832 species and two Paraergasilus Markewitsch, 1937 species have been described from African freshwater habitats since the beginning of the twentieth century. As part of this study, the information for these known species was put together to form a complete review of the freshwater African ergasilids with the distribution, description and drawings of all 12 species included. A substantial amount of research has been conducted from the major systems of Africa, but very little has been done in southern Africa. In this study specimens were collected from the Okavango River and Delta and Lake Malawi using a wide variety of collection methods. After the specimens were examined it was found that the material included four new species, two from each study area. The two new species from the Okavango Delta include Ergasilus sp. A from Synodontis nigromaculatus Boulenger, 1905 and Ergasilus sp. B from Brycinus lateralis (Boulenger, 1900). The seasonality and host specificity of the ergasilids collected from the Okavango Delta was discussed, and it was found that the Ergasilus species are not host specific and are more prevalent in the summer months. The species from Lake Malawi include Ergasilus sp. C from Petrotilapia genalutea Marsh, 1983 and Paraergasilus sp. A from Pseudotropheus tropheops Regan, 1922. A review of all the fish species and parasitic crustaceans collected from Lake Malawi is provided, no conclusion could be made on the seasonality of the ergasilids from Lake Malawi due to a lack of information. A phylogenetic analysis was conducted for all the freshwater Ergasilus species using Oermoergasilus mugiiis Oldewage & van As, 1988 as the outgroup. Finally a taxonomic key was compiled for Ergasilus, including all the known and new species.

Sedert die begin van die twintigste eeu is tien spesies van Egasi/us Von Nordmann, 1832 en twee Paraergasilus Markowitsch, 1937 spesies uit Afrika varswaterhabitats beskryf. As deel van hierdie studie is die kennis oor hierdie twee bekende spesies saamgevoeg in 'n volledige oorsig van die verspreiding, beskrywings en illustrasies van al 12 verteenwordigers van varswater Ergasilidae van Afrika. 'n Groot gedeelte van die navorsing gaan oor die hoof rivierstelsels van Afrika, maar min navorsing is oor suidelike- Afrika gedoen. Vir hierdie studie is verskeie metodes gebruik om eksemplare in die Okavangorivier en -delta en die Malawimeer te versamel. In die material wat versamel is, was daar twee nuwe spesies van elk van die versamelingsgebiede. Die Okavangodelta het twee nuwe spesies opgelewer, nl. Egasi/us sp. A op Synodontus nigromacu/atus Boulenger, 1905 en Ergasilus sp. B op Brycinus latera/is (Boulenger, 1900). Die seisoenaliteit en gasheerspesifisiteit van die Okavangodelta ergasilide word bespreek en dit is bevind dat die Ergasi/us spesies nie gasheer spesifiek is nie en dat hulle meer dikwels in die somermaande voorkom. Die spesies van die Malawimeer sluit in Ergasi/us sp. evan Petroti/apia gena/utea Mars, 1983 en Paraergasi/us sp. A van Pseudotropheus tropheops Regan, 1922 in. 'n Oorsig van al die visspesies en die parasitiese krustasiërs wat uit die Malawimeer versamel is, word gegee. As gevolg van gebrekkige inligting kon geen uitsluitseloor die seisoenaliteit van die ergasilide van die Malawimeer gemaak word nie. 'n Filogenetiese analise vir al die varswater Ergasi/us spp. is gedoen, met die gebruik van Dermoergasi/us mugi/is Oldewage & Van As, 1988 as buitegroep. 'n Taksonomiese sleutel wat al die bekende en nuwe spesies van Ergasilus insluit, is opgestel.
Dissertation (M.Sc. (Zoology and Entomology))--University of the Free State, 2004
Keywords: Southern Africa; Freshwater; Fish parasites; Ergasilids; Morphology; Taxonomy; Copepoda -- Africa -- Identification